PARUNTUK KANA DALAM MEMBINA KARAKTER MASYARAKAT KELURAHAN MALAKAJI KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The results of this study indicate that, the form of preaching Paruntuk Kana in fostering the character of the people of Malakaji Village, Kab. Gowa consists of two forms, the first is Bil-Lisan from Paruntuk Kana using figurative sentences to soften the delivery address to the person. While the form of Bil-Hikmah's da'wah in Paruntuk Kana is present in every sentence that contains social sensitivity to fellow human beings. The opportunities from Paruntuk Kana in fostering the character of the people of Malakaji Village, Kab. Gowa is the use of local languages, schools, and art studios. Meanwhile, the challenges are globalization and modernization.